Frequency of Prostate Cancer Among the Prostatic Tissue Samples- Collected From Different Tertiary Level Hospital in Dhaka City (Bangladesh Journal of Urology, 2020)
Background: Prostate cancer is the development of cancer in the prostate, a gland in the male reproductive system. The cancer cells may spread from the prostate to other area of the body, particularly the bones and lymph nodes. It may initially cause no symptoms. A disease known as benign prostatic hyperplasiamay produce similar symptoms.Objective: To identify the frequency of prostate cancer in prostatic tissue submitted for histopathological examination in selected hospital of Dhaka City.Method: This analytical observational study consists of review of 3914 histopathological reports of prostatic specimen examined in 13 selected tertiary level hospitals in Dhaka city. This study was carried out from January 2007 to December 2009 (three years). All data were compiled, analyzed and appropriate statistical tests were done to make inference.Results: During the study period, among the 2914 histopathological specimen of prostatic tissue, 637(about 16%) cases were diagnosed as prostate cancer (including PIN), 3221 (about 82%) cases were benign prostatic hyperplasia, 53 (1 .35%) were chronic prostatitis and the remaining 3 cases were other rare disease e.g. lipid storage disease etc. Among the prostate cancer, most common was prostatic adenocarcinoma (about 95%); about 3% was Prostatic Intraepithelial Neoplasia (PIN), 1% squamous cell carcinoma arid I % are primary Transtiona1 cell carcinoma (TCC). Most of the patients diagnosed with prostate cancers are of advanced age - between 70 to 80 years (53.46%), and the second peak age is 60- 70 years (34.57 %). Of the prostate cancer cases 8.78% were well differentiated, 34.84% were moderately differentiated and 64.36% were poorly differentiated. The ratio between benign and malignant prostatic disease was about 5:1. Though all the prostatic diseases are common in elderly people, benign prostatic disease occurs more commonly: in younger patients than the prostate cancer.Conclusion: From this study it is evident that the burden of prostate cancer is still low in our context. But the disease seems to be increasing in recent years mainly due to increasing number of aged population. So in near future, the burden of the disease will be increasing throughout the world including our country. Prostate cancer is a slow growing tumor. It has a very sensitive tumor marker (PSA) also. Early diagnosis and proper management certainly improves the prognosis of the disease. There is a screening program for early diagnosis of the disease though it is relatively a costly program. Screening should be considered in persons who have a strong family history of prostate cancer. Every urologist, health policy makers should be aware of the burden of the disease and appropriate planning, necessary manpower & skill development, resource allocation should be made to combat the situation efficiently.Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.88-92